Nitric Oxide Binding Geometry in Heme-Proteins: Relevance for Signal Transduction - Giovanna De Simone; Alessandra di Masi; Diego Sbardella; Paolo Ascenzi; Massimiliano Coletta (Antioxidants, 2024)
Nitric oxide (NO) synthesis, signaling, and scavenging is associated to relevant physiological and pathological events. In all tissues and organs, NO levels and related functions are regulated at different levels, with heme proteins playing pivotal roles. Here, we focus on the structural changes related to the different binding modes of NO to heme-Fe(II), as well as the modulatory effects of this diatomic messenger on heme-protein functions. Specifically, the ability of heme proteins to bind NO at either the distal or proximal side of the heme and the transient interchanging of the binding site is reported. This sheds light on the regulation of O2 supply to tissues with high metabolic activity, such as the retina, where a precise regulation of blood flow is necessary to meet the demand of nutrients.